A collaborative supply chain inventory model with defective items, adjusted production rate and variable lead time. (2016) - Jauhari, Wakhid Ahmad; Sejati, Nelita Putri; Rosyidi, Cucuk Nur
This paper proposes a production-inventory model for supply chain system consisting of single-vendor and single-buyer. The buyer uses periodic review policy to manage his inventory. The lead time is formulated by considering production time and transportation time. Moreover, the demand in buyer side is assumed to be normally distributed and the shortage is assumed to be fully backordered. The production process maybe deteriorated during production time hence the lot received by the buyer may contain some defective items. The defective rate of the items is assumed to be fixed. The objective of the proposed model is to determine review period, production rate and number of deliveries to minimise the joint total cost. An iterative procedure is proposed for finding the solutions of the model. A numerical example and sensitivity analysis are illustrated to show the model's behaviour.